Cultural dimensions impact on customer’s expectations about the hotel service: application in different HDI Latin countries - Franco, Mara (2020)
Due to its dynamic nature and its importance in the service process definition, customer’s expectations have been hardly studied, however, very few focused on the impact of culture on customer’s expectations formation, as customer’s can belong to different cultures. Also, the study of customer’s expectations about tourism services has increased, mostly applied in developed countries from the north hemisphere. Still, countries from different hemispheres have different levels of social and economic development and therefore, can differ in the way that culture influences customers’ expectations about services in groups of countries with different levels of human development. In this sense, the main purpose of this research is to understand if cultural dimensions influence customers’ expectations about a service equally in groups of countries with different levels of human development. The multigroup analysis using structural equation modelling was used to calculate the regression weights for all the path combinations in analysis for each proposed group of countries with different levels of human development. This research regarded the hotel service and data was collected from ten Latin countries: Portugal, Spain, France, Italy, Romania, Brazil, Mexico, Uruguay, Bolivia, and Chile. About 1262 customers answered a questionnaire about their expectations about service dimensions of the hotel service and their cultural dimensions. Findings show that cultural dimensions influence in customers’ expectations about hotel service is not equal in groups of countries with different levels of human development (HDI). Theoretically the major contribution is the application of a cross-cultural approach that demonstrated that cultural dimensions influence customers’ expectations about the hotel service differently in developed and in development countries with different levels of social and economic development. Therefore, it also indicates that hotel managers will have to adapt the service according to the level of human development of each group of countries in an internationalization process.